2020
DOI: 10.1371/journal.pone.0236147
|View full text |Cite
|
Sign up to set email alerts
|

Visual attention outperforms visual-perceptual parameters required by law as an indicator of on-road driving performance

Abstract: A variety of visual and psychometric tests have been developed for assessing on-road driving performance and fitness to drive. The diagnostic power of a state of the art psychometric test battery (Vienna Test System) combined with a set of standard visual parameters recommended for assessing fitness to drive is investigated using an on-road driving test. The study aimed to determine whether a psychometric test battery could predict older adults' onroad driving performance. The relevance of visual standards req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Moreover, no significant differences have been found when comparing the driving skills of a group of very old drivers aged 80 to 89 years with those of a second group aged 90 years and older (Hollis et al, 2013). Overall, these findings suggest that advanced age alone is not a determinant of driving competence and that other variables should be considered to identify at-risk drivers (Grundler & Strasburger, 2020).…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Moreover, no significant differences have been found when comparing the driving skills of a group of very old drivers aged 80 to 89 years with those of a second group aged 90 years and older (Hollis et al, 2013). Overall, these findings suggest that advanced age alone is not a determinant of driving competence and that other variables should be considered to identify at-risk drivers (Grundler & Strasburger, 2020).…”
Section: Introductionmentioning
confidence: 70%
“…First, over the age of 80, chronological age seems to be a poor predictor of drivingrelated cognitive performances. In this regard, other studies have argued against the efficacy screening polices for elderly drivers based on chronological age (Dobbs, 2008;Grundler & Strasburger, 2020;Siren & Meng, 2012). Second, the results of factorial analyses showed that motor and processing speed reflect latent abilities related to but different from the other cognitive abilities tested.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Glaucoma patients show altered eye movement behavior compared to the normal population while watching TV [17]. Apart from clinical testing, knowledge about qualityof-life (QoL) of glaucoma patients helps to understand the progression of the disease [31]. Thus awareness of the disease improves the QoL utilizing compensatory head and eye movements towards the visual field loss.Different studies have shown a correlation between clinical measures and eye gaze parameters in glaucoma patients than normal participants.…”
Section: Literature Surveymentioning
confidence: 99%
“…Some reports have attempted to compare these perceptual visual parameters to the more holistic concept of visual attention, which combines the two aspects with psychometric performance and is anticipated to be more discriminative. 8,9 The main challenge of this approach might be its feasibility and the potential for its conversion into driving prerequisites and legal dispositions.…”
Section: Vision Impairment and Traffic Safety Outcomes In Lmicsmentioning
confidence: 99%